Improvement of executive functions after the application of a neuropsychological intervention program (PEFEN) in pre-term children. (March 2019) - García-Bermúdez, Olga; Cruz-Quintana, Francisco; Pérez-García, Miguel; Hidalgo-Ruzzante, Natalia; Fernández-Alcántara, Manuel; Pérez-Marfil, Mª. Nieves
Abstract: Prematurity is one of the most prevalent health problems in developed countries. It is associated with important clinical and educational consequences, problems in activities of daily life, as well as alterations in different domains of executive functions (EF).The objective of the present study was to evaluate the effectiveness of a stimulation program for the EF (PEFEN Program) in a group of premature children and compare the effects with a control group, who worked with routine curricular skills. The participants were children aged 4 and 5 years, born preterm between 32 and 37 weeks of gestation with a weight between 1500 and 2499 g, without severe chronic pathology, or disability equal to or >33% (mental, sensorial and/or motor).The participants were evaluated individually using the BENCI, CUMANIN, and BRIEF-P neuropsychological tests, before and after both interventions. The results showed that the preterm-children who received the PEFEN program significantly improved in the domains of verbal understanding, phonic fluency, verbal fluency, working memory, visual memory, verbal memory, rhythm, and attention, in comparison with the control group. It is recommended to implement programs such as PEFEN to improve the development of EF in the school environment and prevent the deficit in populations at risk. Highlights: The application of EF stimulation programs improves neuropsychological performance in preterm children. Neuropsychological domains such as memory, attention and EF improve after the application of the program. The PEFEN program has shown its usefulness in premature children.